Pelatihan Manajemen Organisasi Bagi Himpunan Mahasiswa Jurusan Prodi MPI STAI Jam’iyah Mahmudiyah Langkat - Rani Febriyanni; Novira Arafah (Fusion: Jurnal Pengabdian kepada Masyarakat, 2025)
Student organization management is a learning forum for students to develop themselves in organization, leadership, and learning to carry out activities, ranging from academic to non-academic ones. The purpose of the student organization was established, namely to create an internal campus government institution with the aim of helping achieve the vision of a university. The method used in Community Service (PkM) is qualitative using a descriptive approach. The results of community service are the management strategy of the HMJ organization of MPI STAI Jam'iyah Mahmudiyah Langkat students in preparing work program designs that will be realized using SWOT analysis to achieve the desired results. SWOT analysis is a management tool used to identify strengths, weaknesses, opportunities and threats. This analysis can help organizations understand the conditions of work programs that will be launched before they are realized and formulate strategies based on these findings. The following is an example of how SWOT analysis can be applied in identifying student organization work programs.